State-Owned Enterprises Finance from the Perspective of State Funds - Sopian Sitepu (Universitas Airlangga, 2019)
The existence of State-Owned enterprises (SOE) as one of Indonesia’s legal entities, whereby the State owns part of all of the capital of the company has presented several legal issues. The BUMN Act that has become the basis for establishing State-Owned enterprises has become its own independent legal subject and separates itself from the wealth of the State and has adhered to the provisions of the Company Law Act so that the capital that is presented by the State to the corporation remains as the capital of the SOE and not form the State. However, existing legislations regarding State funds places the funds for SOE as being part of the State budget. This ambiguity in the status of BUMN Funds is not only found in legislations but also in two different constitutional court decisions that presents inconsistencies towards law enforcers. This clear distinction is crucial in the practice of law enforcement in Indonesia.